Facile Electrochemical Intramolecular Amination of Urea‐Tethered Terminal Alkenes for the Synthesis of Cyclic Ureas. Issue 8 (9th July 2018) - Ahmed, Nisar; Khatoon, Saira
Abstract: Facile intramolecular amination of unactivated alkenes has been achieved by using electricity as a catalyst that helps to generate an intermediate and accelerates formation of cyclic ureas in high yields. Using this method, no metal catalysts were used. During electrolysis, a nitrogen radical was formed at the urea substrate that cyclised with the alkene and generated a terminal carbon radical which further formed a bond with the 2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl radical (TEMPO). This method of electrolysis not only gives cyclic ureas but also functionalises terminal unactivated alkenes. This method can be considered to be environmentally friendly given that it avoids the issues of toxicity or complicated metal ligands and could therefore be potentially employed in green chemistry. Abstract : Go green : Several reagents and reagent combinations have been developed for the amination and functionalisation of unactivated alkenes. However, most of these are dependent on oxidants and catalysts. Herein, we report a green approach for the intramolecular amination of urea‐tethered alkenes by generating radicals without using expensive catalysts and employing only electricity.